Analysis of Alzheimer's Disease-Related Mortality Rates Among the Elderly Populations Across the United States: An Analysis of Demographic and Regional Disparities from 1999 to 2020 - Khan, Abdul Hadi; Ijaz, Eman; Ubaid, Bushra; Eddaki, Ilias; Edhi, Maliha; Shah, Muhammad Nauman; Perry, George (Current Alzheimer Research, 2024)
IntroductionAlzheimer’s Disease (AD) is the leading cause of dementia and a significant public health concern, characterized by high incidence, mortality, and economic burden. This study analyzes the mortality patterns and demographic disparities in Alzheimer's disease-related deaths among the elderly population in the United States from 1999 through 2020.MethodsAlzheimer's disease mortality data for individuals 65 and older were obtained from the CDC WONDER database, utilizing ICD-10 codes G30.0, G30.1, G30.8, and G30.9 for identification. Demographic and regional variables included age, gender, race/ethnicity, place of death, urban-rural status, and geographic region. Crude death rates (CR) and age-adjusted mortality rates (AAMR) per 100,000 individuals were calculated. Joinpoint Regression Program 5.0.2 was used to analyze trends, calculating Annual Percentage Changes (APCs) and Average Annual Percentage Changes (AAPCs).ResultsFrom 1999 to 2020, 1,852,432 deaths were attributed to AD among individuals aged 65 and older. The AAMR increased from 128.8 in 1999 to 254.3 in 2020, with an AAPC of 2.99% (95% CI = 2.61-3.48). The age-adjusted mortality rate (AAMR) was higher in females (218.5) than in males (163.5). Among racial and ethnic groups, non-Hispanic whites had the highest AAMR, followed by Non-Hispanic Blacks and Hispanics. Regionally, the West reported the highest AAMR, while the Northeast recorded the lowest. Most deaths occurred in nursing homes (57.3%), with a significant portion also occurring at decedents' homes (22.4%).ConclusionAD mortality rates in the U.S. have risen significantly, with notable disparities across age, gender, race, and geographic regions. These findings highlight the need for targeted interventions and research to address the growing burden of AD, particularly among the most affected demographic groups.
Keywords: mortality trends